FEATURES OF TRANSLATING VIETNAMESE DISH NAMES INTO RUSSIAN (Journal of Foreign Language Studies, 2025)
This article analyzes the features of the translation of Vietnamese dishes’ names into Russian from the perspectives of linguistics and translation theory. The research aims to identify existing problems and determine the dominant strategy used in translating Vietnamese dishes’ names into Russian. The research methods include statistical analysis and component analysis. The results show that transliteration/transcription of Vietnamese dishes’ names into Russian still faces some inconsistencies, partly due to variations in transliteration/transcription rules for borrowed words from Vietnamese proposed by different authors. Furthermore, existing transliteration/transcription rules only apply to Vietnamese personal names and toponyms. Therefore, the paper suggests the need to establish transliteration/transcription rules for other Vietnamese loanwords groups. Moreover, the analysis reveals that the preferred strategy for translating food names from Vietnamese to Russian is foreignization combined with clarifications.
Keywords: translation; menu; Vietnamese loanwords; domestication; foreignization